2018
DOI: 10.1017/s0022215118001548
|View full text |Cite
|
Sign up to set email alerts
|

Stapedotomy using a 4 mm endoscope: any advantage over a microscope?

Abstract: ObjectivesTo ascertain the feasibility of endoscopic (4 mm) stapedotomy, and compare intra- and post-operative variations with microscopic stapedotomies.MethodsForty otosclerosis patients were scheduled for microscopic or endoscopic stapedotomy. Intra-operative variables compared were: incision, canalplasty, canal wall curettage for ossicular assessment, chorda tympani manipulation, ability to perform stapes footplate perforation before its supra-structure removal, and operative time. Post-operative variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…32,33 Nevertheless, like any other newly introduced technology, this innovative approach has a learning curve for every surgeon not acquainted with endoscopic otology. 16,[18][19][20]23,34 In line with this view, Iannella and Magliulo reported that operative duration seemed to decrease with greater experience. 15 The Journal of Laryngology & Otology However, as the microscopic technique is of great importance and cannot be entirely substituted, ENT trainees should be enrolled in augmented learning curricula, combining microscopic and endoscopic ear surgery teaching, allowing optimal performance in otological surgery.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…32,33 Nevertheless, like any other newly introduced technology, this innovative approach has a learning curve for every surgeon not acquainted with endoscopic otology. 16,[18][19][20]23,34 In line with this view, Iannella and Magliulo reported that operative duration seemed to decrease with greater experience. 15 The Journal of Laryngology & Otology However, as the microscopic technique is of great importance and cannot be entirely substituted, ENT trainees should be enrolled in augmented learning curricula, combining microscopic and endoscopic ear surgery teaching, allowing optimal performance in otological surgery.…”
Section: Discussionmentioning
confidence: 87%
“…Based on five studies, 13,1618,20 the pooled air–bone gap after endoscopic and microscopic stapes surgery was 9.08 dB (95 per cent CI = 7.06, 11.10) and 10.79 dB (95 per cent CI = 7.82, 13.75), respectively. In the absence of statistical heterogeneity ( I 2 = 51.57 per cent, p Q = 0.08), there was no difference in terms of success rate between the two treatments (pooled mean difference = −0.20; 95 per cent CI = −0.53, 0.14) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations